A Precious‐Metal‐Free Hybrid Electrolyzer for Alcohol Oxidation Coupled to CO2‐to‐Syngas Conversion. (18th May 2020) - Bajada, Mark A.; Roy, Souvik; Warnan, Julien; Abdiaziz, Kaltum; Wagner, Andreas; Roessler, Maxie M.; Reisner, Erwin
Abstract: Electrolyzers combining CO2 reduction (CO2 R) with organic substrate oxidation can produce fuel and chemical feedstocks with a relatively low energy requirement when compared to systems that source electrons from water oxidation. Here, we report an anodic hybrid assembly based on a (2, 2, 6, 6‐tetramethylpiperidin‐1‐yl)oxyl (TEMPO) electrocatalyst modified with a silatrane‐anchor (STEMPO ), which is covalently immobilized on a mesoporous indium tin oxide ( meso ITO) scaffold for efficient alcohol oxidation (AlcOx). This molecular anode was subsequently combined with a cathode consisting of a polymeric cobalt phthalocyanine on carbon nanotubes to construct a hybrid, precious‐metal‐free coupled AlcOx–CO2 R electrolyzer. After three‐hour electrolysis, glycerol is selectively oxidized to glyceraldehyde with a turnover number (TON) of ≈1000 and Faradaic efficiency (FE) of 83 %. The cathode generated a stoichiometric amount of syngas with a CO:H2 ratio of 1.25±0.25 and an overall cobalt‐based TON of 894 with a FE of 82 %. This prototype device inspires the design and implementation of nonconventional strategies for coupling CO2 R to less energy demanding, and value‐added, oxidative chemistry. Abstract : Inspirational device : A molecularly engineered electrolyzer was constructed for the selective oxidation of glycerol to glyceraldehyde, with a turnover number (TON) of ≈1000 and a Faradaic efficiency (FE) of 83 %, coupled with aqueous CO2 reduction to generate a stoichiometric amount of syngas, with a CO:H2 ratio of 1.25±0.25, an overall TON of 894 and FE of 82 %.